CONSUMER ADOPTION OF MOBILE SHOPPING APPLICATIONS: EMPIRICAL EVIDENCE FROM INDIA (Lex localis - Journal of Local Self-Government, 2025)
Purpose: This study aims to investigate the factors influencing consumers’ intention to use mobile shopping applications in India by applying a well-established technology acceptance model (TAM) as a theoretical framework.Design / methodology / approach: The study sample comprises 205 respondents with a response rate of 82 percent. To test the hypothesis, analysis of a moment structures (AMOS) was performed on the data using CFA and SEM.Findings: The findings of this study revealed that personal innovativeness emerged as a significant determinant of consumers' adoption of m-shopping applications in India. Moreover, perceived usefulness and perceived ease of use are additional factors that are positively correlated with their adoption.However, perceived risk does not have a substantial effect on Indian consumers’ intention to use m-shopping applications.Practical implications: From a practical standpoint, this research would support app developers and online retailers in their efforts to persuade consumers to try and stick with their mobile shopping apps. Additionally, it helps researchers and academicians to have a deeper understanding of the various factors that influence consumers’ intention towards the use of mobile shopping applications.Research limitation: The findings of this study have limited generalizability because it focuses solely on India.Originality / value: This study made a substantial contribution by elucidating the factors that can influence the adoption of mobile shopping applications. The present study has effectively extended the TAM to encompass m-shopping applications through the integration of personal innovativeness. Extended TAM offers a more comprehensive understanding of consumers’ adoption of m-shopping applications in India.